Association of nephrotoxic medication exposure and nephrotoxic medication induced acute kidney injury in hospitalised non-critically ill children: single centre study - Keerthiga, N.; Fernando, M. Edwin; Murugesan, V.; Prasad, N. D. Srinivasa; Valavan, S. Thiruma; Abirami, P. (International Journal of Advances in Medicine, 2025)
Background: Acute kidney injury (AKI) in children is increasingly linked to nephrotoxic medication exposure, particularly in hospitalized patients. Although nephrotoxic drugs contribute substantially to AKI incidence, especially with multiple-agent exposure, data on their prevalence and associated AKI risk in non-critically ill pediatric populations remain limited. This study assessed the prevalence of nephrotoxic medication exposure in non-critically ill children per 1000 patient-days of hospitalization, and the prevalence of nephrotoxic AKI among these patients. Methods: This prospective study evaluated nephrotoxic medication exposure and the development of nephrotoxic AKI in non-critically ill hospitalized children aged 1 month to 12 years. Baseline kidney function was assessed and serum creatinine levels were monitored during and after the exposure period. AKI was defined according to KDIGO criteria. Upon AKI occurrence, nephrotoxic medications are substituted with less harmful alternatives. Results: The study included 3,264 children with bronchopneumonia (29.4%), acute gastroenteritis (26%), and tropical fever (22.4%) as common hospitalization causes. Nephrotoxic medication exposure was identified in 3.1% of cases, yielding a prevalence rate of 5.02 per 1000 patient days. Most exposed children were aged 3 to 12 years (58.4%), with a nearly equal gender distribution (males: 51.5%). Among those exposed, 70.3% received one nephrotoxic medication, while 29.7% received two, resulting in an AKI prevalence of 5.94%. AKI resolved within an average of 11±4 days following the substitution of non-nephrotoxic drugs. The most frequently administered nephrotoxic drugs were vancomycin (38.6%), acyclovir (26.7%), and amikacin (17.8%). Conclusions: The findings indicate that nephrotoxic medication exposure among non-critically ill children was minimal, with a low prevalence rate of nephrotoxic AKI. Vancomycin, acyclovir, and amikacin are the most commonly used nephrotoxic drugs.